BMP4/LIF or RA/Forskolin Suppresses the Proliferation of Neural Stem Cells Derived from Adult Monkey Brain. (20th September 2017) - Han, Xinxin; Yu, Liming; Chen, Qingqing; Wang, Min; Ren, Jie; Wang, Guangming; Chen, Yihong; Lu, Lixia; Tian, Haibin; Chen, Li; Zhang, Ying; Liu, Yuehua; et al.
Abstract : Monkeys are much closer to human and are the most common nonhuman primates which are used in biomedical studies. Neural progenitor cells can originate from the hippocampus of adult monkeys. Despite a few reports, the detailed properties of monkey neural stem cells (NSCs) and their responses to cytokine are still unclear. Here, we derive NSCs from an adult monkey brain and demonstrate that BMP4 inhibits cell proliferation and affects cell morphology of monkey NSCs. Combined treatment of BMP4 and LIF or RA and Forskolin represses the proliferation of monkey NSCs. We also show that BMP4 may promote monkey NSC quiescence. Our study therefore provides implications for NSC-based cell therapy of brain injury in the future.